Bioinspired roll-to-roll solar-thermal energy harvesting within form-stable flexible composite phase change materials. Issue 40 (14th September 2020) - Chang, Chao; Nie, Xiao; Li, Xiaoxiang; Tao, Peng; Fu, Benwei; Wang, Zhongyong; Xu, Jiale; Ye, Qinxian; Zhang, Jingyi; Song, Chengyi; Shang, Wen; Deng, Tao
Abstract : Roll-to-roll charging of flexible composite phase change materials enables fast solar-thermal energy harvesting within bulk storage media. Abstract : Converting solar energy into storable thermal energy within organic phase change materials has emerged as a promising way to overcome solar intermittency and continuously harness solar-thermal energy for many heating-related applications. The low thermal conductivity and leakage issue of the phase change materials, however, limit scalable solar-thermal energy storage and their practical applications. Inspired by the dynamic thermoregulation behavior of butterfly wings, here we demonstrate rapid roll-to-roll solar-thermal energy harvesting within flexible form-stable composite phase change materials. Instead of static charging the bulk materials, the thin composite sheets are exposed to solar radiation for rapid charging while being continuously rolled. Due to shortened heat-diffusion distance and rollability of the composites, it achieves fast uniform solar-thermal energy storage within the bulk storage media. The flexibility of charged composites also enables broad tuning of the discharging behavior, and offers the possibility to explore wearable thermotherapy and other flexible solar-thermal applications.